Fair ball - Jeter, Derek, 1974-; Mantell, Paul (Simon & Schuster Books for Young Readers, 2017)
"Derek is juggling finals and a baseball tournament during the last few weeks of school, but when his friend Dave starts ignoring him, Derek's perfect summer starts to look less fun"--